Pembelajaran Sejarah Pada Siswa SMK Dengan Menggunakan Metode Guided Noted Taking - Wahyuni Nurhidayati (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This article was written with the aim of being a reference in the selection of innovative and fun learning methods in learning history for vocational students using the Guided Noted Taking method. The process of implementing learning uses handout media which contains a description of the material by eliminating important parts whose purpose is to be completed by students. The purpose of using this handout is to train students' focus and concentration during learning. The learning step with this method begins with the selection of appropriate teaching materials, making material handouts, giving the blank parts of the handout. The research method used is Systematic Literature Review (SLR).